Pengembangan Media Interaktif Kvisoft Flipbook Maker Pada Pembelajaran Bahasa Indonesia - Yuliana Kurniasari; M. Subandowo; Hari Karyono (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The aims this development is to produce Kvisoft Flipbook Maker Interactive Media in Indonesian as a source of information that is of particular interest and is also expected for students as a whole. The development model used in the development of this interactive learning multimedia is the ADDIE model. The development stages in the ADDIE model consist of five stages which include analysis, design, development, implementation, evaluation. The development process involves subject content experts, learning design experts and learning media experts to provide feedback and input for improvements. In addition, the Indonesian Subject teacher as a user of the Kvisoft Flipbook Maker Interactive Media also provides feedback and input. Based on the results of the research, several conclusions can be drawn as follows: (1) The development of Kvisoft Flipbook Maker Interactive Media was developed based on an analysis of the needs of teachers and students through a needs questionnaire provided by the developer, (2) Validation results of material experts, media experts, and product design experts development of Kvisoft Flipbook Maker Interactive Media with very feasible criteria to be developed, and (3) Based on the results of research on the development of Kvisoft Flipbook Maker Interactive Media it can be concluded that Kvisoft Flipbook Maker Interactive Media learning media is used in developing abilities in designing creative, innovative and interesting learning.